A potential gasing as folk games product towards commercialized product in Malay craft / Nur Fadhilah Mohd Omar - Mohd Omar, Nur Fadhilah (2015)
Gasing or "Top Spinning" is one of the famous Malay traditional heritage games. It comes in many designs and names. The game is performed by a combination of two players. This Gasing is recognized as intangible traditional games by the National Heritage Department, Meanwhile, National Craft Malaysia has categorized this product as one the art crafts in Folk Games category. The Ministry of Tourism and Culture is responsible to monitor and supervised the development of Gasing. Developing and introducing this game to Malaysia and the world seems have difficulties. This research aims to explore the physical characteristics of the design of Gasing and at the same time to identify to study and process of making design as well as how the product development is being carried out. The tasks are to analyze and identify the Gasing for the game and the one as a craft item in Malaysia. Several interview sessions have been conducted to get information on Gasing from selected craftsmen in Melaka, Perak, Kelantan, Johor and Pahang. Observation method has also been carried out to observe and analyze the process of making Gasing. The research outcome will be recorded reference in developing the so called commercialized Gasing and can be used as a guidance to keep the genuinely and popularity of this game for future. The new potential derived from the research may help to preserve this heritage product and as an identity of the traditional game in this challenging global market. The findings for this research showed have seven characteristic in designing Gasing found with this research.